2021
DOI: 10.1007/s11356-021-12670-x
|View full text |Cite
|
Sign up to set email alerts
|

Amitraz induced cytotoxic effect on bovine cumulus cells and impaired oocyte maturation

Abstract: The aim of this study was to evaluate the genotoxic and cytotoxic effects of amitraz (AMZ) on the primary culture of bovine cumulus cells (CC) and oocyte nuclear maturation. Cytotoxicity was evaluated by assessing mitochondrial activity with the 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. Genotoxicity was estimated using the alkaline single cell gel electrophoresis (SCGE) assay. Apoptosis was detected with the Annexin V-affinity assay. The in vitro maturation test was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The location of formazan formation and its intracellular transportation has remained controversial. While the role of mitochondria in MTT reduction [ 2 , 4 , 5 ] has been a justification for the common application of the assay to measure mitochondrial activity [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], biochemical and microscopic studies have located formazan in various intracellular organelles. Intracellular formazan granules have been observed in the endoplasmic reticulum, cytosolic lipid droplets [ 13 , 14 ], plasma membranes [ 1 , 15 ], nucleus, and microsomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of formazan formation and its intracellular transportation has remained controversial. While the role of mitochondria in MTT reduction [ 2 , 4 , 5 ] has been a justification for the common application of the assay to measure mitochondrial activity [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], biochemical and microscopic studies have located formazan in various intracellular organelles. Intracellular formazan granules have been observed in the endoplasmic reticulum, cytosolic lipid droplets [ 13 , 14 ], plasma membranes [ 1 , 15 ], nucleus, and microsomes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed limitations of the MTT assay [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ] and various confounding factors that are needed to be considered in designing, performing, analyzing, and interpreting the assay results [ 5 , 9 , 10 , 11 , 12 , 13 , 14 ]. However, the MTT assay is still commonly used and interpreted, overlooking these limitations and escaping the necessary optimization steps.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of indole on cell proliferation and morphology were evaluated by label-free cell count and brightfield microscopy at 24 h post-transfection. This method was preferable to e.g., MTT assay due to fewer limitations to assay validation [53][54][55][56][57][58][59][60][61] such as interferences from potentially confounding factors, e.g., cell culture variations, DMSO, optical effects, cell manipulation, and transfection effects on metabolic activity [62][63][64][65][66][67][68][69][70][71][72][73]. Cells were imaged at 40X magnification using the high contrast brightfield detection channel of the Cytation 1 Cell Imaging Multi-Mode Reader (BioTek CYT1FAV).…”
Section: Cell Proliferation and Morphologymentioning
confidence: 99%